THE EFFECT OF CHANGES IN ORGANISATION AND ORGANISATION CULTURE TOWARDS EMPLOYEE’S PERFORMANCE THROUGH JOB SATISFACTION OF MILLENNIALS GENERATION IN PT X NORTH SUMATERA BRANCH - Siti Safira Mayhara; Yeni Absah; Amlys Syahputra Silalahi (RADJA PUBLIKA, 2023)
This study uses research variables such as organizational change (structure, technology, arrangement, human resources management), organization culture and employee’s performance. The purpose of this study was to determine the effect of changes in organization towards employee’s performance, the effect of organization culture towards employee’s performance to the employee millennial generation of PT X North Sumatera branch. The approach used in this study is an associative approach and the population in this study are generation “Y” employees of PT X North Sumatra branch. While the samples that met the sampling criteria, the withdrawal of observations was made amounted to 84 people which is non probability sampling that fulfil terms and conditions to be respondent. The data collection technique in this study used a questionnaire technique. Data analysis techniques in this study use Partial Least Square (PLS). Data processing in this study using the SmartPLS 3.0 software program. The results show that changes in organization affects toward employees performance and organizational culture affects toward employees performance at PT X North Sumatera branch.